Case report: Kaposi hemangioendothelioma of the right upper limb with the Kasabach–Merritt phenomenon: A potentially lethal diagnostic challenge - Belani, Levin; Sapuan, Jamari; Abdullah, Shalimar; Hing, Erica Yee; Loh, C-Khai; Alias, Hamidah (Frontiers in Pediatrics, 2022)
Kaposi Hemangioendothelioma (KHE) is a rare vascular neoplasm which presents usually within the first year of life. Due to its rarity and complexity, there is often a delay in diagnosis. KHE could be associated with a life-threatening consumptive coagulopathy of Kasabach-Merritt Phenomenon (KMP). We present a case of a 2-month-old baby girl who presented with progressive redness and swelling of her right upper limb over 6 weeks. She presented to multiple health practitioners who misdiagnosed her as an insect bite, cellulitis and necrotizing fasciitis and the treatment deemed futile. Full blood count revealed bicytopenia of anemia and thrombocytopenia, a normal coagulation cascade and a low fibrinogen and raised D-Dimer levels. The imaging was suggestive of a high flow vascular tumor likely to be a KHE. Subsequently, she was started on a single agent oral Sirolimus with dose increment to achieve therapeutic level and was treated for 1 year. She successfully completed the treatment and only had transient hypertriglyceridemia which resolved upon completion of treatment. Currently, she is in remission at 3 years off treatment. We would like to highlight the potentially lethal misdiagnosis of KHE with KMP, the importance of an early diagnosis of this condition, and the successful outcome with a single agent Sirolimus.